2020
DOI: 10.4103/sjg.sjg_213_20
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of aryl hydrocarbon receptor repressor (AHRR) gene in gallbladder cancer

Abstract: Background: The aryl hydrocarbon receptor repressor (AHRR), a member of the growing superfamily, is a basic helix-loop-helix/PerAHR nuclear translocator (ARNT)-Sim (bHLH-PAS) protein. AHRR has been proposed to function as a putative new tumor suppressor gene based on studies in multiple types of human cancers. This current study aims to investigate AHHR expression and its prognostic significance in gallbladder cancer. Methods: The study includes 48 gallbladder cancer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In this study, we found that muscle-invasiveness is significantly associated with higher AhRR percent methylation, hence a higher repression of its transcription. This is supported in the literature, where AhRR is suggested to play a key role in tumor suppression and the fact that the expression of AhRR is downregulated in various cancer tissues [39][40][41][42]. AhRR repression may contribute to aggressive tumorigenic phenotype, including increased migration and invasiveness, and reduced apoptosis in cancer cells [41].…”
Section: Discussionmentioning
confidence: 55%
“…In this study, we found that muscle-invasiveness is significantly associated with higher AhRR percent methylation, hence a higher repression of its transcription. This is supported in the literature, where AhRR is suggested to play a key role in tumor suppression and the fact that the expression of AhRR is downregulated in various cancer tissues [39][40][41][42]. AhRR repression may contribute to aggressive tumorigenic phenotype, including increased migration and invasiveness, and reduced apoptosis in cancer cells [41].…”
Section: Discussionmentioning
confidence: 55%